Management strategies of dental anxiety and uncooperative behaviors in children with Autism spectrum disorder - Shi-Jun Tang; Hong-Lin Wei; Cai-Yu Li; Ming-Na Huang (BMC, 2023)
Abstract Background Children with Autism spectrum disorder (ASD) was frequently experienced dental anxiety and uncooperative behaviors during dental treatment. Oral health care was necessary because of the poor oral hygiene and prevalent dental diseases in this population. Aim In this systematic review, we evaluated the effectiveness and feasibility for pediatric dentist to manage the dental anxiety in children with ASD. Design PubMed, Embase, and Cochrane Library were systematically performed on the literature search. The date of eligible publications was from inception to January 2023. After that, the quality of eligible studies was assessed by the Newcastle Ottawa Scale (NOS). Review findings were summarized using the PRISMA Statement for reporting. Results A total of six studies were systematically evaluated according to the inclusion and exclusion criteria. Five studies were conducted to evaluate ASD Children's anxiety and uncooperative performance in the progressive oral examination, oral disease prophylaxis and fluoride application. The other one study evaluated the success rate of treatment in decayed permanent tooth treatment. In the included studies, four studies indicated that it was extremely necessary to reduce dental anxiety of ASD children to increase the cooperation in sensory-adapted dental environment (SADE). Conclusion It is not always effective and feasible for pediatric dentist to manage the dental anxiety in children with autism during routine oral examination. Meanwhile, it is necessary for ASD children to conduct preoperative psychological assessment, to investigate parents' expectations and cooperation, and to determine whether to start corresponding dental treatment.